Analisis Bahan Ajar Akidah Madrasah Ibtidaiyah (Studi Kritis atas Buku Membina Akidah Akhlak Karya Wiyadi) - M. Mujib Hidayat (Edukasia Islamika : Jurnal Pendidikan Islam, 2018)
The implementation of aqidah (matters of faith) into the soul is one of effective ways in creating elements of goodness which aims to make people able to do their duty well. The determination of implementing akidah as one of subjects in Islamic elementary school is an exact way in creating devout generation who have faith and good behavior because it functions to improve students’ behavior, sanctify their soul, and direct them to the noble and moderate Islamic values. Therefore, in this case, the role of akidah as a subject, should be constructed from the right materials related to the field of divinity and behavior education. This study belongs to library research by using philosophical ontology approach. The aim of this study is to find out the essence of a book entitled “Membina Akidah Akhlak” as one of akidah learning materials used in Islamic elementary school. Moreover, it also tries to analyze its conformity with the curriculum applied as well as jumhur al-mutakallimin.